Strategies of Islamic Religious Education Teachers in Preventing Bullying Behavior in Elementary Schools: A Case Study at SDN 005 Bontang Selatan - Irmawati; Amaluddin; Muhammad Nur Maallah; Andi Fitriyani Djollong (EDUJAVARE: International Journal of Educational Research, 2026)
Bullying behavior among elementary school students remains a pressing educational concern because of its direct impact on students’ sense of security, self-confidence, learning motivation, and mental development. This study aims to identify the forms of bullying behavior, analyze its implications for students’ learning mentality, and uncover the strategies employed by Islamic Religious Education (PAI) teachers in preventing, addressing, and minimizing bullying at SDN 005 Bontang Selatan. A qualitative case study design was employed, informed by theological, pedagogical, and psychological paradigms. Primary data were obtained from the principal, PAI teacher, and classroom teacher through observation, semi-structured interviews, and document study, analyzed through data reduction, data display, and conclusion drawing, with validity established through source and method triangulation. The findings reveal that bullying manifests in verbal, social/relational, mild physical, and non-verbal forms, contributing to diminished feelings of safety, self-esteem, motivation, and classroom climate. PAI teachers implement layered strategies that are preventive, curative, educational, collaborative, and disciplinary, positioning themselves as educators, role models, counselors, motivators, mediators, and collaborators. This study contributes novel insight into the PAI teacher’s role as an “empathy catalyst” and identifies the phenomenon of “joke-bullying,” which requires deliberate deconstruction of students’ perceptions of humor. These findings offer theoretical and practical contributions toward developing an Islamic character education model for bullying prevention in elementary schools.